Efficacy of Intense Pulsed Light in the Treatment of Recurrent Chalaziosis - Zhu, Yirui; Huang, Xiaodan; Lin, Lin; Di, Mengshu; Chen, Ruida; Dong, Jilian; Jin, Xiuming (Frontiers in Medicine, 2022)
Purpose High recurrence rate of chalaziosis and serious side effects of repeated surgical excision may help increase awareness of recurrent and refractory chalaziosis as a serious disorder affecting many aspects of life. This present study was aimed to investigate the efficacy and safety of intense pulse light (IPL) therapy and meibomian gland expression (MGX) in cases of recurrent chalaziosis after excision surgery. Methods Forty-two consecutive recurrent chalaziosis cases (35 patients) treated with IPL-MGX were enrolled. All patients initially underwent excision with curettage. One week after lesion excision, IPL-MGX were performed at least 3 times. Another set of age- and sex-matched consecutive cases of recurrent chalaziosis, who received excision with curettage, but went without IPL-MGX treatment, were collected to calculate recurrence rate. Treatment efficacy and safety were measured before IPL-MGX treatment and 1 month after the final treatment. Results The majority of patients received 4 sessions of IPL-MGX therapy (20 patients; 57.1%) or 3 sessions of IPL-MGX therapy (10 patients; 28.6%), resulting in a lower recurrence rate of 11.4% compared to that of recurrent chalaziosis without IPL-MGX cases (45.6%, P < 0.001). The NIBUT was significantly prolonged from 3.9 ± 1.8 to 5.1 ± 1.7 s at 4 weeks after the final treatment (P = 0.001). Similarly, mean TMH score improved and was statistically significant when compared with baseline (0.17 ± 0.07 vs. 0.21± 0.09; P = 0.008). Furthermore, meibum quality and expressibility scores significantly improved at 4 weeks following the final treatment (both P < 0.001). Other variables, such as intraocular pressure and visual acuity, remained unaffected following treatment. Conclusion The combination of IPL treatment and MGX offers a low risk and effective option in decreasing the recurrence rate of recurrent chalaziosis by improving meibomian gland function. IPL-MGX may be considered for first-line treatment in recurrent or refractory cases post excision.